G-CSF induction early in uropathogenic Escherichia coli infection of the urinary tract modulates host immunity - Ingersoll, Molly A. (2008)
Uropathogenic Escherichia coli (UPEC), the causative agent of approximately 85% of urinary tract infections (UTI), is a major health concern primarily affecting women. During infection, neutrophils infiltrate the bladder, but the mechanism of recruitment is not well understood. Here, we investigated the role of UPEC-induced cytokine production in neutrophil recruitment and UTI progression. We first examined the kinetics of cytokine expression during UPEC infection of the bladder, and their contribution to neutrophil recruitment. We found that UPEC infection induces expression of several pro-inflammatory cytokines including granulocyte colony-stimulating factor (G-CSF, CSF-3), not previously known to be involved in the host response to UTI. G-CSF induces neutrophil emigration from the bone marrow; these cells are thought to be critical for bacterial clearance during infection. Upon neutralization of G-CSF during UPEC infection, we found fewer circulating neutrophils, decreased neutrophil infiltration into the bladder and, paradoxically, a decreased bacterial burden in the bladder. However, depletion of G-CSF resulted in a corresponding increase in macrophage-activating cytokines, such as monocyte chemotactic protein-1 (MCP-1, CCL-2) and Il-1β, which may be key in host response to UPEC infection, potentially resolving the paradoxical decreased bacterial burden. Thus, G-CSF acts in a previously unrecognized role to modulate the host inflammatory response during UPEC infection.